Organizational Citizenship Behavior Ditinjau dari Komitmen Orgnisasi pada Guru di Sekolah Swasta Methodist-2 Medan - Jessica Yustan; Diny Atrizka; Achmad Irvan Dwi Putra (Mahesa Research Center, 2019)
This study aims to find relationship between organizational commitment and organizational citizenship behavior (OCB). The hypothesis of this study states that there is a positive relationship between organizational commitment and organizational citizenship behavior (OCB). The subjects of this study were teachers in Methodist-2 private school Medan consisting of 110 subjects selected by using purposive sampling method. Data were obtained from a scale to measure organizational commitment and OCB. Analysis of the data used is Pearson Product Moment Correlation with SPSS 20.00 for Windows program. The results of this research showed a correlation of 0.388 (p <0.05) and showed that there is a positive relationship between organizational commitment and organizational citizenship behavior. The results of this study indicate that the contributions made by the variable organizational commitment to the OCB was 15,1 percent and the remaining 84,9 percent is influenced by other factors that are not examined. From these results it is concluded that the hypothesis is acceptable.